Las microalgas como indicadores de contaminación del canal de Pasaje en las aguas del Río Jubones de la provincia de El Oro. - Fernández Suriaga, Patricio S. (2005)
The present investigation work is carried out it for not having a lot of information on this topic. They took several samples of the waters of the Río Jubones in the Channel Pasaje to these samples they are carried out determination of the pH with a portable pHmetro, determination of the oxygenate with a Oxigenometro.